The upshot of Polyphenolic compounds on immunity amid COVID-19 pandemic and other emerging communicable diseases: An appraisal - Khalil, Ayman (Nat Prod Bioprospect, 2020)
Polyphenols are a large family of more than 10,000 naturally occurring compounds, which exert countless pharmacological, biological and physiological benefits for human health including several chronic diseases such as cancer, diabetes, cardiovascular, and neurological diseases. Their role in traditional medicine, such as the use of a wide range of remedial herbs (thyme, oregano, rosemary, sage, mint, basil), has been well and long known for treating common respiratory problems and cold infections. This review reports on the most highlighted polyphenolic compounds present in up to date literature and their specific antiviral perceptive properties that might enhance the body immunity facing COVID-19, and other viral infectious diseases. In fact, several studies and clinical trials increasingly proved the role of polyphenols in controlling numerous human pathogens including SARS and MERS, which are quite similar to COVID-19 through the enhancement of host immune response against viral infections by different biological mechanisms. Thus, polyphenols ought to be considered as a potential and valuable source for designing new drugs that could be used effectively in the combat against COVID‐19 and other rigorous diseases.